Dukungan Keluarga Dengan Kepatuhan Minum Obat ARV Pada Pasien HIV (Human Immunodeficiency Virus) Di Poli VCT RSUD Dr. R. Koesma Tuban - Fahmana, Nur Lutfiyah; Su’udi, Su’udi; Sumiatin, Titik (Jurnal Ilmiah Wahana Pendidikan, 2024)
HIV (Human Immunodeficiency Virus) sufferers need to be treated to reduce the amount of virus in the body and prevent opportunistic infections and their complications, antiretrovirals (ARVs) are consumed for life, on time, and with discipline. Based on the available data, there are still many patients who do not adhere to treatment. The purpose of this study is to analyze the VCT Polyclinic at RSUD dr. R. Koesma Tuban, namely the Relationship between Family Support and Compliance with Taking ARV Medicine in HIV Patients.Collaborative analytic research design with a cross-sectional approach. The study population was 227 HIV patients who were taking ARV treatment at the VCT Polyclinic at RSUD dr. R. Koesma Tuban from a sample of 138 patients. The sampling technique used is purposive sampling. The research variable is independent family support, the dependent variable is adherence to taking ARV medication. Data collection was carried out using a questionnaire which was analyzed using the Spearman Rank Correlation test.The results showed that most (65.9%) patients had good family support, and most had good medication adherence (64.5%). After the Spearman Rank Correlation test was carried out, it was obtained p = 0.000 with p <0.05 indicating a strong significant relationship between family support and adherence to taking ARV medication (0.691) with a result of p = 0.000 with p <0.005.This shows that family support is very important for HIV patients to take treatment, because with good family support HIV patients are obedient in taking treatment.